Novel Silica-Based Hybrid Adsorbents: Copper(II) Adsorption Isotherms and Thermodynamics - Hu, Keyan; Liu, Junsheng; Chen, Xinghua; Xu, Min; Wang, Kechun (Asian Journal of Chemistry, 2014)
In this study, copper(II) adsorption isotherms and thermodynamic data have been investigated using a hybrid membrane as an adsorbent. It is found that copper(II) adsorption on sample D followed the Freundlich isotherm model. Moreover, it is found that the adsorption capacity of copper(II) on sample D increases with an increase in solution temperature and the DG values are changed from positive to negative as the temperature increased, suggesting that copper(II) adsorption is an endothermic and spontaneous in nature as the solution temperature was elevated to higher level. In addition, based on intraparticle diffusion, it is confirmed that copper(II) adsorption is not governed by intraparticle diffusion and diffusion-controlled adsorption mechanism might be the major control process. This finding is meaningful in the removal of copper(II) from aqueous solution using hybrid membrane as an adsorbent.